POLYGLANDULAR AUTOIMMUNE SYNDROME TYPE 3: THE UNEXPECTED TRILOGY - Jasmiad , Nurbadriah; Abdullah, Noor Rafhati Adyani (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Polyglandular autoimmune syndromes (PGAS) are a rare group of disorders characterized by the presence of two or more autoimmune endocrine diseases. Polyglandular autoimmune syndrome type 3 (PGAS-3) is characterized by the presence of autoimmune thyroid disease associated with other autoimmune diseases excluding adrenal insufficiency and hypoparathyroidism. This case report focuses on a patient who developed a sequential presentation of pernicious anemia, Graves’ disease, and later type 1 diabetes mellitus (T1DM), raising suspicion for PGAS-3. CASE A 30-year-old male presented in 2019 with fatigue, weight loss, and palpitations. Initial investigations revealed pancytopenia with Hb 4 mmol/L, WBC 3.99 mmol/L, PLT 87 mmol/L and a critically low vitamin B12 level, alongside positive anti-parietal cell antibodies, indicative of pernicious anemia. Oesophagogastroduodenoscopy (OGDS) was done later in 2023, showing pangastritis. Concurrently, the patient was found to have hyperthyroidism with positive thyroid antibodies, consistent with Graves’ disease. He was treated with subcutaneous cyanocobalamin and antithyroid medications, resulting in partial improvement. He underwent radioactive iodine therapy for Graves’ disease. Four years later, the patient was hospitalized for uncontrolled diabetes mellitus. Insulin autoantibodies were requested and results of anti-islet cell antibodies, anti-glutamic acid decarboxylase and anti-insulinoma-associated antigen-2 were positive, leading to the diagnosis of T1DM. Adrenocorticotropic hormone (ACTH) and early morning serum cortisol were normal, excluding adrenal involvement. The coexistence of Graves’ disease, pernicious anemia, and T1DM fulfilled the diagnostic criteria for PGAS-3. Genetic testing and further autoimmune screening were recommended for a more comprehensive understanding of the underlying pathophysiology. CONCLUSION The patient’s progression from pernicious anemia to Graves’ disease followed by T1DM is consistent with polyglandular autoimmune syndrome type 3. Clinicians should be vigilant in identifying PGAS in patients with multiple autoimmune endocrine disorders to ensure appropriate diagnosis and treatment, mitigating its potential long-term consequences.